Economic valuation of cactus pear production in semi-arid regions of Tunisia - Louhaichi, Mounir; Hamdeni, Imtinene; Slim, Slim; Hassan, Sawsan; Harbeg, Lamia; Ghouhis, Fethi (International Society for Horticultural Science, 2022)
Arid and semi-arid lands are considered unsuitable for crop production because they require substantial amounts of water and additional nutrients. However, certain species can perform well and enhance the livelihoods of poor farmers. In the semi-arid regions of Tunisia, cactus pear (Opuntia ficus indica L. Mill.) is a potential subsistence fruit and forage plant. Sixty questionnaire surveys were conducted in Kairouan and Sidi Bouzid Provinces to assess the cost and benefits of cactus pear cultivation for feed and fruit production. Results showed that cactus pear production systems are characterized by low inputs; 85% of the farmers surveyed are using cactus pear for animal feed during the summer and fall compared to 26 and 37% in winter and spring. Fifty percent of the annual cactus pear cladode production (between 10 and 40 t ha‑1) is used for livestock feeding. Fruit productivity ranged between 1 to 5 t ha‑1 with an average of 2.5 t ha‑1. Both fruits and cladodes are harvested manually. The estimated net profitability of 1 ha of cactus pear is about 800 USD (32% fodder production and 62% fruit production). Farmers in semi-arid regions of Tunisia are practicing traditional production system techniques. However, with the new technologies available, a wide range of products based on fruits and cladodes can be obtained, which can increase cactus pear profitability. Hence, efforts are needed to train farmers. We concluded that cactus pear cultivation would strengthen agro-pastoral system resilience by mitigating the negative impacts of climate change and enhancing pastoralist incomes.